Linear atrophoderma of Moulin: an underrecognized entity - Zahedi niaki, Omid (Pediatr Rheumatol Online J, 2015)
Linear atrophoderma of Moulin (LAM) is an acquired skin condition that manifests in early childhood and adolescence. It likely represents a form of cutaneous mosaicism that presents with linear, hyperpigmented and atrophic lesions appearing on the trunk and limbs. Its clinical appearance varies and may closely resemble that of atrophoderma of Pasini and Pierini (APP) and linear scleroderma. LAM usually follows a benign course and no effective treatment options exist. We present a case of a young and healthy patient that developed such lesions on her upper and lower extremities over 5 years. The initial clinical impression of linear scleroderma was reviewed in favor of LAM following histological examination of the lesions which revealed no significant inflammatory changes. LAM remains a rare and possibly under recognized entity with reports confined only to the dermatologic literature. This case highlights the importance of recognizing LAM and distinguishing it from linear scleroderma given the significant differences in management and prognosis.